Assessment of Sensory Processing and Executive Functions in Childhood: Development, Reliability, and Validity of the EPYFEI - Romero-Ayuso, Dulce; Jorquera-Cabrera, Sara; Segura-Fragoso, Antonio; Toledano-González, Abel; Rodríguez-Martínez, M. Carmen; Triviño-Juárez, José Matías (Frontiers in Pediatrics, 2018)
The aim of this study is to present the psychometric properties of a questionnaire whose objective is to assess the sensory processing and executive functions of children aged between 3 and 11, which was designed to be fillied in by their parents or carers. The Evaluation of Sensory Processing and Executive Functions in Childhood (EPYFEI) was completed by a sample of 1385 parents (n=1385) of children aged between 3 and 11 from Spain. An explanatory factorial analysis was then carried out, which showed four principal factors: 1) executive attention and work memory; emotional self-regulation; 3) propioceptive and vestibular sensory processing, and 4) tactile processing and alert regulation. The reliability of the analysis was high for the set of the questionnaire and the factors of which it is composed. The results obtained provide evidence regarding the the potetial usefulness of the EPYFEI in clinical contexts and for the early detection of neurodevelopment disorders, in which there may be a lack as regards executive functions and sensory processing.